Upaya Meningkatkan Kemampuan Membaca dan Menulis melalui Media Pembelajaran Interaktif Digital melalui Aplikasi Gemar (Game Membaca Lancar) pada Peserta Didik Kelas 2 SDN Cinunuk 01 - Azka Aulia Azzahrah; Tin Rustini (Departement of Mathematics Education, 2023)
Learning media can be an effective tool in helping overcome delays in reading and writing in grade 2 students, but the learning media developed must be innovative and digital media so that students easily understand and with the latest systems. Data collection techniques, researchers conduct student observations, educator interviews and journal literature studies. Data collection was carried out with the results of interviews with grade 2 educators of SDN Cinunuk 01 who carried out teaching activities. There are delays in reading and writing in these two students, there are several factors experienced. Based on the results of observation, the main cause of this delay in reading writing is environmental and psychological factors. Gemar or Fluent Reading Game is an application that can be accessed by students easily. In this hobby application, students can learn interactively. By using the Gemar digital application, students can easily read and rewrite what has been read by students